Obstetric Risk Factors and Anal Incontinence among Women with Previous History of Vaginal Delivery - Azizah Nurdin; Trika Irianta; Mardiah Tahir; Maisuri T. Chalid (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To investigate the obstetric risk factors of the analincontinence in mothers with previous history of vaginaldelivery.Methods: The was a case-control study conducted in the Obstetricsand Gynecology Department of Dr.Wahidin Sudirohusodo Hospital,Faculty of Medicine, Universitas Hasanuddin, Makassar, during theperiod of February 2015 through January 2016. The researchinstruments were used to evaluate obstetric risk factors and theanal incontinence was the self-administered questionnaire and FecalIncontinence Severity Index. The data were analyzed statisticallyusing the Chi-square test with the significant value of p<0.05.Results: A total of 300 subjects were recruited in this study. Theresearch results indicated that the parity of ï‚³ 3, the assisted vaginaldelivery history (vacuum extraction), and the prolong secondstage of labor had a significant correlation with the anal incontinencewith p value=0.026, OR (95% CI) = 1.8 (1.07-3.03), p=0.018with OR (95% CI) =3.65 (1.2-10.7) and p=0.006 with OR (95% CI)= 2.9 (1.2-6.7).The history of episiotomy and the delivery of thebaby ï‚³ 4000 gram had no correlation with the anal incontinence.Conclusion: Parity, vacuum delivery and prolong second stage oflabor have an association with anal incontinence among womenwho has history of vaginal delivery.Keywords: anal incontinence, obstetric risk factors, vaginal delivery